From data opacity to data literacy: co-producing welfare transparency through decile-based public information socialization at the village level - Roziqin, Rafli Miftakhul; Fadiya, Salwa; Maulana, Abdi Luhung; Putri, Talita Benita Agus; Pratiwi, Zaskia Indah; Kinasih, Mutiara Lintang; Shodiq, Azka Kurniawan; Solihati, Adinda Dwi Nur; Gibran, Darrell; Salsabila, Nadia Septiya; Fadillah, Tyas; Purwonugroho, Tunggul Adi (Priviet Social Sciences Journal, 2026)
Transparency in social assistance governance remains a key challenge in improving targeting accuracy and public trust, particularly at the village level. This community service study examines the impact of decile-based public information socialization on community understanding of social assistance distribution and the Kartu Indonesia Sehat (KIS) program in Banjareja Village, Kebumen Regency. Using a pre-experimental one-group pre-test–post-test design, data were collected from 32 participants, including village officials and RT/RW representatives. Community understanding was measured using a structured questionnaire administered before and after the socialization activity. Owing to the non-normal data distribution, differences between the pre-test and post-test scores were analyzed using the Wilcoxon Signed-Ranks Test. The results indicate a statistically significant improvement in community understanding following the socialization activity (p < 0.05). The findings suggest that combining public information transparency with interactive discussions enhances policy literacy and supports participatory engagement in social assistance governance. The involvement of local actors reflects the practice of co-production, in which communities actively contribute to understanding and monitoring welfare policies. This study highlights the importance of participatory, data-informed socialization as a practical approach to strengthening transparency, accountability, and community engagement in social assistance programs at the village level.